The influence of Krakow Technology Park on the development of Małopolska: an impact study - Pach, Janina (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2015)
Cracow Technology Park with the status of a special economic zone is a unique combinationof the idea of a technology park and a special economic zone. This allows it to have an intergal impacton the development of Malopolska region in a multidimensional way: - Economic, including business development, creation of new work places, growth of the economicpotential of the region due to broadly defined new investments,etc. - Environmental, connected with environment protection and the implementation of modern environmentfriendly solutions, - Infrastructural, including the development of areas such as: roads, transport, computerization, internet,etc., - Technical and technological, due to collaboration between entrepreneurs and research institutionssuch as Cracow universities, - Socio-cultural, associated with: the education level, the effects of imitation, changes in incomeand consumption patterns, etc., - Spatial, relating to changes in the management of Malopolska region by developing new sites, locatingof new companies and institutions.